Relation & effect of Human resources management strategic with at work stress : Explorative study - جثير سعدون حمود; حسين حسين وليد (Journal of Economics and Administrative Sciences, 2016)
Abstract The mine object for this research is determine the nature of the relation and effect between Human resources management strategic to less the work stress , Human resources management strategic represent a set of procedures and practices to manage the human resources at the organization. the stress of work effect on the performance of the human resources , al rasheed bank select to applied the qustioneer on the 32 person the work on the sebaa branch , using the qustioneer as a tool to collect data that is design according some of the standards and make the validity and stability. to analyses this data by using spss for computation " percentage , mean , standard , deriation , coefficient sperman , the simple inear regression". the resulte refer to the significant relationship between the Human resources management strategic and the decreasing the stress of work. the researcher recomendate this organization th in crease intrest on the Human resources management strategic and its tools.